Enhancing parental health literacy through educational workshops: improving care for children with complex health needs - Sarah Thomas; Hannah Zhu; May Yip; Kathryn Moore; Jin Khaw; Javairia Yakoob; Hemavathy Palanyiaya (BMJ Paediatrics Open)
We conducted a workshop to enhance parental health literacy for managing children with complex health needs. Parents identified key areas requiring support, including puberty, toileting and seizure management. Specialist-led interactive sessions were held, with pre-event and post-event surveys assessing changes in parental confidence. Results showed significant improvements in understanding, with confidence scores rising across all topics, particularly in puberty (2.7 to 4.2) and feeding support (4 to 5). Over 90% of attendees reported the workshop met expectations. This study highlights the benefits of co-production in education and suggests further research into long-term impacts and larger-scale interventions.